Developing Islamic Values in Response to the Social Dynamics and Technology Advancement | تطوير قيم الشريعة الإسلامية في استجابة ديناميات المجتمع والتقدم التكنولوجي - Abdul Wahab Abdul Muhaimin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
In response to the dynamics of society and the development of modern science and technology, there is a necessity to develop the values of Islamic sharia based on the Qur'an and Hadith by interpreting the verses of the Qur'an, explaining the hadith of the prophet and paying attention to the purposes of Sharia. This paper, therefore, intends to describe and demonstrate some development of Islamic values in worship field and medical treatment field. The article specifies on performing the prayers in travelling and pilgrim ritual for the former, and artificial insemination and human cloning for the later.